The freshwater copepod genus \(Mesocyclops\) (Copepoda, Cyclopoida, Cyclopidae) in Vietnam - Luong, Tran Duc; Thanh, Dang Ngoc; Hai, Ho Thanh (Academia Journal of Biology, 2020)
The freshwater copepod Mesocyclops Sar, 1914, a species-rich genus within the family Cyclopoidae Rafinesque, 1815, is common in tropical areas. In addition, the genus members are used for the biological control of mosquito larvae (Anopheles, Aedes) which are vectors for transmitting dengue fever. In Vietnam, a total of 11 Mesocyclops species have been recorded in inland freshwater bodies. Of which, one endemic species (M. sondoongensis Tran & Hołyńska, 2015) and two species were described from Vietnam, namely M. yenae Hołyńska, 1998; M. ferjemurami Hołyńska & Vu, 2000. Diagnostic characteristics, habitat, and distribution of all 11 species are provided. Additionally, a pictorial key to all Vietnamese Mesocyclops is presented.